2022
DOI: 10.1097/j.pain.0000000000002627
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced carbonic anhydrase mediated dorsal horn neuron activation and induction of neuropathic pain

Abstract: Supplemental Digital Content is Available in the Text.Reduced spinal cord blood flow leads to a hypoxia-mediated activation of hypoxia inducible factor 1α in dorsal horn neurons. This results in a carbonic anhydrase–dependent neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…In addition to MASTL, carbonic anhydrase 3, F-box leucine-rich repeat protein 4 (FBXL4), and NADH-ubiquinone oxidoreductase chain 4L also differed signi cantly between the two groups. Carbonic anhydrase 3 is an intracellular protein that acts as a metabotropic inhibitor of inositol triphosphate receptor 1 (ITPR1), which is essential for intracellular Ca 2+ release, synaptic function, chronic pain, and neuronal excitability (33), and studies have shown that inhibition of carbonic anhydrase activity reduces hypoxia-induced pain (34)(35)(36). In addition, it has been suggested that inhibitors of human carbonic anhydrase 3reduce abnormal pain caused by neuropathy in mice (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MASTL, carbonic anhydrase 3, F-box leucine-rich repeat protein 4 (FBXL4), and NADH-ubiquinone oxidoreductase chain 4L also differed signi cantly between the two groups. Carbonic anhydrase 3 is an intracellular protein that acts as a metabotropic inhibitor of inositol triphosphate receptor 1 (ITPR1), which is essential for intracellular Ca 2+ release, synaptic function, chronic pain, and neuronal excitability (33), and studies have shown that inhibition of carbonic anhydrase activity reduces hypoxia-induced pain (34)(35)(36). In addition, it has been suggested that inhibitors of human carbonic anhydrase 3reduce abnormal pain caused by neuropathy in mice (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our work has presented that damage and cessation of blood flow in the spinal cord vasculature also initiates chronic pain states(Ved et al ., 2018 a ). This is further emphasised by the induction of hypoxia in the microenvironment of the dorsal horn neurons driving chronic pain states(Da Vitoria Lobo et al ., 2022). The spinal cord vasculature, which comprises of largely of endothelial cells (EC), degenerates either through endothelium apoptosis or regression, and is implicated in the onset of numerous neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal cord vasculature, which comprises of largely of endothelial cells (EC), degenerates either through endothelium apoptosis or regression, and is implicated in the onset of numerous neurological diseases. Our work presented to date highlights that if the endothelium degenerates exclusively, pain manifests(Ved et al ., 2018 a ; Da Vitoria Lobo et al ., 2022). However, it remains undefined the cellular and/or molecular events that underpin the diminishing health of the dorsal horn endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…All rodents were habituated to the testing environment prior to nociceptive behavioural experimentation [3,22]. Mechanical withdrawal thresholds were acquired following application of Von Frey (vF) hairs to the plantar surface of the hindpaw.…”
Section: Methodsmentioning
confidence: 99%